Efficacy of percutaneous endoscopic lumbar discectomy (PELD) combined with sinuvertebral nerve ablation versus PELD for low back pain in lumbar disc herniation - Yanjun Huang; Shangshu Wei; Shuyue Yang; Yanzhu Shen; Haoning Ma; Ping Yi; Xiangsheng Tang (Journal of Orthopaedic Surgery and Research)
Abstract Background Percutaneous endoscopic lumbar discectomy (PELD) has demonstrated variable efficacy in alleviating low back pain (LBP) associated with lumbar disc herniation (LDH). Sinuvertebral nerve ablation (SNA), which targets the nociceptive pathway implicated in discogenic LBP pathogenesis, has emerged as a potential adjunctive therapy. The efficacy of endoscopic radiofrequency ablation in enhancing PELD for the treatment of LBP in patients with LDH remains unclear. Methods A retrospective cohort study was conducted on LDH patients with concomitant LBP treated at the Spinal Surgery Department, China-Japan Friendship Hospital, from June 2020 to June 2023. Participants were categorized into two groups: PELD combined with SNA (n = 51) and PELD alone (n = 46). Primary outcome measures included the Visual Analog Scale (VAS) for pain, the Japanese Orthopaedic Association (JOA) score, and the Oswestry Disability Index (ODI) at baseline and 1-, 3-, and 6-month follow-ups. Results Both groups exhibited significant improvements in VAS, JOA, and ODI scores for LBP and leg pain postoperatively compared to preoperative assessments. Notably, the PELD combined with SNA group demonstrated statistically significant superior outcomes in VAS, JOA, and ODI scores specifically for LBP compared to the PELD group. Conclusion The combination of PELD with SNA significantly improves LBP outcomes compared to PELD alone in LDH patients. While the observed improvements did not reach the minimal clinically important differences (MICD), these findings suggest that SNA may enhance the efficacy of PELD in LBP management.